Secondary prevention of reproductive system tumors in women living in the urban and rural environments - I.P. Aminodova; M.D. Vasiliev; E.V. Makarova; V.I. Makarova (LCC «Medicine-Inform», 2023)
I.P. Aminodova1-3, M.D. Vasiliev1, E.V. Makarova1, V.I. Makarova1 1N.A. Semashko National Research Institute of Public Health, Moscow, Russian Federation 2Autonomous Non-commercial Organization Medical Center "White Rose", Ivanovo, Russian Federation 3Ivanovo State Medical Academy, Ivanovo, Russian Federation Aim: to analyze specific aspects of diagnosing reproductive system disorders in women depending on the place of residence, medical activity and awareness of the female population, staffing resources and the availability of equipment in medical institutions. Patients and Methods: the analysis covered medical records of 9,785 women who, at their own volition, visited the medical center for medical check-up. Gynecological examination, colposcopy, liquid-based cytology, pelvic and breast ultrasound examination, and mammography were performed in all patients. The patients were asked to fill out a questionnaire including the following data: conditions of life and work, lifestyle, and risk factors of malignant tumors of the female reproductive system. Results and Discussion: women over 40 years of age were more concerned about their health status. Thus, it is necessary to find mechanisms for the additional motivation of women of early and middle reproductive age for expanding the screening coverage. It was found out that the differences in the organization of secondary prevention of reproductive system tumors in women living in the urban and rural environments are underpinned by the impact of demographic and social factors, characteristics of medical activity of the population, and staffing shortages in healthcare institutions. These aspects should be taken into consideration for developing methods aimed at overcoming the current failures in the diagnostic process. Conclusion: the establishing of regional "Women's Health Centers" based on multi-disciplinary comprehensive approach will help to improve the detection of tumors of the female reproductive system at the pre-cancer stage, facilitate the timely identification and mitigation of the risk factors of tumor development, and to ensure the prevention of recurrences and progression of hyperplastic processes of the reproductive system in women. Keywords: tumors of reproductive system, prevention, diagnosis, organizational measures. For citation: Aminodova I.P., Vasiliev M.D., Makarova E.V., Makarova V.I. Secondary prevention of reproductive system tumors in women living in the urban and rural environments. Russian Journal of Woman and Child Health. 2023;6(2):112-118 (in Russ.). DOI: 10.32364/2618-8430-2023-6-2-112-118.